Analisis Lokasi, Persepsi Konsumen Dan Kualitas Pelayanan Terhadap Loyalitas Konsumen Pada Chanet Babarsari Yogyakarta - Lahura, Armando; Welsa, Henny; Maharani, Bernadetta Diansepti (Universitas Muhammadiyah Metro, 2023)
AbstractThis study aims to determine (1) the effect of location on consumer loyalty (2) the effect ofconsumer perception on consumer loyalty (3) the effect of service quality on consumer loyalty.The sample in this study were 150 consumers of Chanet Babarsari Yogyakarta who had used theservices of the cafe Chanet Babarsari Yogyakarta. The data collection method used aquestionnaire method which was distributed with the Accidental Purposive Sampling technique.In this study using Data Quality Test, Classical Assumption Test, and Multiple Regression Test.The results of this study indicate (1) there is a positive and significant influence of Location onConsumer Loyalty (2) there is a positive and significant effect of Consumer Perception onConsumer Loyalty (3) there is a positive and significant influence on Service Quality onConsumer Loyalty.Keywords: Location, Consumer Perception, Service Quality and Consumer Loyalty.